Knowledge, attitude, and acceptance of COVID-19 vaccine in pregnant women - Arissara Kuptarak; Vorapong Phupong (Therapeutic Advances in Vaccines and Immunotherapy)
Background: Due to the COVID-19 situation, vaccination is a key factor in reducing the severity and transmission of the disease, especially in the vulnerable population, which includes pregnant women. Currently, various policies are in place to promote the vaccination of pregnant women against COVID-19; however, some pregnant women decline vaccination. Objectives: To study pregnant women’s knowledge, attitude, and acceptance regarding the COVID-19 vaccine. Design: A cross-sectional study was conducted among pregnant women who received antenatal care at King Chulalongkorn Memorial Hospital, Chulalongkorn University, Bangkok, Thailand. Methods: Pregnant women who received antenatal care at King Chulalongkorn Memorial Hospital, Chulalongkorn University from November 2021 to April 2022 were included. The participants answered an online questionnaire through their electronic devices. Univariate and multivariate logistic regression analyses were performed to analyze the data. Results: A total of 500 pregnant women participated in this study. Among them, 67.4% and 81.4% had great knowledge and a positive attitude toward the COVID-19 vaccine, respectively, with scores of 80% or higher in each section. Of the 500 participants, 468 (93.6%) accepted to receive the COVID-19 vaccine. After adjusting for certain variables through multivariate analysis, the factor associated with the decision to receive the COVID-19 vaccine was having great knowledge about the vaccine (adjusted odds ratio (OR) 13.25, 95% confidence interval (CI) 2.45–71.61). However, the most significant factor associated with the decision to reject the COVID-19 vaccine was the recent COVID-19 infection (adjusted OR 0.11, 95% CI 0.02–0.62). Conclusion: The COVID-19 pandemic presents severe and life-threatening conditions for both pregnant women and their fetuses. The majority of the pregnant women in this study had great knowledge and acceptance of the vaccine and a positive attitude toward it. The pregnant women who had prior knowledge of the vaccine tended to accept to receive it during pregnancy, whereas those who recently contracted COVID-19 were hesitant to receive the vaccine.